2014
DOI: 10.1016/j.bbrc.2013.12.071
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the N-terminal portion of influenza virus RNA polymerase subunit PB1 in nucleotide recognition

Abstract: The influenza virus PB1 protein functions as a catalytic subunit of the viral RNA-dependent RNA polymerase and contains the highly conserved motifs of RNA-dependent RNA polymerases together with putative nucleotide-binding sites. PB1 also binds to viral genomic RNAs and its replicative intermediates through the promoter regions. The detail function and interplay between functional domains are not clarified although a part of structures and functions of PB1 have been clarified. In this study, we analyzed the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Ribavirin and 5-azacytidine exhibited comparable activity in this assay, with 2 to 3 log 10 reductions in influenza virus titer at 10 M. 5-Fluorouracil was less potent, with similar reductions at 80 M. The A/Panama/2007/1999 (H3N2) strain appeared to be less sensitive to both ribavirin and 5-fluorouracil than the other three strains. This strain is not known to be inherently resistant to these drugs and does not contain either PB1 D27N or PB1 V43I, two mutations that are known to confer ribavirin resistance (32,45). The reduced sensitivity could be due to the reduced replicative capacity of A/Panama/2007/1999 in MDCK cells, where its average titer of 3.2 ϫ 10 5 TCID 50 /ml in the absence of drug was at least 1.5 log 10 lower than those of the other strains.…”
Section: Anti-influenza Virus Effects Of Nucleoside Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribavirin and 5-azacytidine exhibited comparable activity in this assay, with 2 to 3 log 10 reductions in influenza virus titer at 10 M. 5-Fluorouracil was less potent, with similar reductions at 80 M. The A/Panama/2007/1999 (H3N2) strain appeared to be less sensitive to both ribavirin and 5-fluorouracil than the other three strains. This strain is not known to be inherently resistant to these drugs and does not contain either PB1 D27N or PB1 V43I, two mutations that are known to confer ribavirin resistance (32,45). The reduced sensitivity could be due to the reduced replicative capacity of A/Panama/2007/1999 in MDCK cells, where its average titer of 3.2 ϫ 10 5 TCID 50 /ml in the absence of drug was at least 1.5 log 10 lower than those of the other strains.…”
Section: Anti-influenza Virus Effects Of Nucleoside Analogsmentioning
confidence: 99%
“…Within host cells, it alters GTP pool concentrations by inhibiting IMP dehydrogenase (IMPDH) (29,30). Other modes of action may include direct inhibition of the influenza virus RdRp (31,32) and interference with capping of viral RNA (33). Some data suggest that ribavirin affects inflammatory and T-cell responses in vivo (34)(35)(36).…”
mentioning
confidence: 99%
“…In some cases, however, the precise mechanisms of resistance remain unclear and fidelity may or may not be involved. In the Orthomyxoviridae, an influenza A virus variant D27N, in the PB1 catalytic subunit of the viral replicase, was isolated that displays higher activity than wild type virus in the presence of RBV, as well as of an inhibitor of purine biosynthesis, methotrexate [7]. The authors suggest that this residue is involved in nucleotide recognition, but whether resistance results from increased fidelity or from increased processivity remains to be determined.…”
Section: Ribavirin and Its Isolated Resistant Variantsmentioning
confidence: 99%
“…In recent years, these studies have focused on whether RBV is directly inhibiting the RdRp, mutagenizing the genome, inhibiting IMPDH, or a combination of the three.Inhibition of RNA synthesis is observed for the influenza virus polymerase in cells treated with either RBV or methotrexate, an inhibitor of purine synthesis that decreases intracellular concentrations of purines. In this case, loss of polymerase activity at low concentrations of nucleotide is considered to be the culprit [7]. For hepatitis E virus (HEV) replication in vitro, RBV has the same antiviral effect as two other IMPDH inhibitors, mycophenolic acid (MPA) and 5-ethynyl-1-b-D-ribofuranosylimidazole-4-carboxamide (EICAR) that can be neutralized by the addition of guanosine.…”
mentioning
confidence: 99%
“…This helix ␣1 domain contains a crucial, highly conserved PB1 basic residue, Arg-45, that is involved in NTP binding and nucleotidyltransferase reactions. Our group reported that a single amino acid mutation in the PB1 helix ␣1 domain induced changes in nucleotide recognition and the viral RNA synthesis reaction (40,41). To examine the structural effects of V43I substitution, we built a homology model using the PB1 polymerase of bat/Guatemala/060/2010 (H17N10), with which PR8-PB1 shares 79% identity, as a template (38) (Fig.…”
Section: Discussionmentioning
confidence: 99%